Facebooking for a Lively Interaction in Literature Classes A Case study of Master I Teachers and Students at the Department of English – Laghouat University - Lebtar ,Nabila; Boumediene , Houda (Faculty of Letters and Foreign Languages Department of English, 2018)
Facebook is a social network site which is universally-adopted as a good tool of communication. It can enhance interaction and engagement between different members and even learners. On the other hand, literature has a high position in the language classes particularly in EFL classes. It becomes an essential component for learners to master. Furthermore, teachers of English Literature are always thinking about how to bring new and effective tools of interaction so as to enhance students’ better understanding of literary lessons. In this respect, Facebook may be a useful tool. Thus, the purpose of this study is to investigate the impact of integrating Facebook as a tool of interaction in literature classes, and its effects on improving students’ performance in literature. In order to achieve this objective, the researcher selects (50) students from Master One as a sample and (7) teachers from the English Department in Laghouat University - Algeria. The method adopted was descriptive and our data were collected through two questionnaires. Even though, Facebook usage has some disadvantages, the results indicate that both teachers and students have a positive attitude towards the use of Facebook in learning literature. During this study, the researcher discovered that Facebook was able to make a lively interaction in literature classes. It was able to strength the relationship among students themselves and between them and their teachers. And hence, we can recommend the integration of Facebook by EFL teachers to add an enjoyable interaction in the educational contexts in the future